2016
DOI: 10.5194/amt-9-3053-2016
|View full text |Cite
|
Sign up to set email alerts
|

Real time retrieval of volcanic cloud particles and SO<sub>2</sub> by satellite using an improved simplified approach

Abstract: Volcanic plume removal (VPR) is a procedure developed to retrieve the ash optical depth, effective radius and mass, and sulfur dioxide mass contained in a volcanic cloud from the thermal radiance at 8.7, 11, and 12 µm. It is based on an estimation of a virtual image representing what the sensor would have seen in a multispectral thermal image if the volcanic cloud were not present. Ash and sulfur dioxide were retrieved by the first version of the VPR using a very simple atmospheric model that ignored the layer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…For the distal monitoring, VCTH is computed by applying the same procedure described for the VPTH parameter but considering the whole volcanic cloud, while the ash and SO 2 detection and retrievals are obtained by exploiting the SEVIRI channels centred at 8.7, 10.8, and 12 µm (SEVIRI channels 7, 9, and 10, respectively). The detection is realized through a Red Green Blue (RGB) composite obtained by combining the brightness temperatures (T b ) of the three SEVIRI channels (R: T b,8.7 -T b,10.8 ; G: T b,12 -T b,10.8 ; B: T b,10.8 ), while the quantitative estimation of the different ash and SO 2 parameters are computed by exploiting the Volcanic Plume Retrieval (VPR) procedure, formerly Volcanic Plume Removal [16][17][18]50]. VPR requires in input only the VCTH and is based on the computation of a new image by replacing the radiance values in the region occupied by the plume with those obtained from a simple linear regression of the radiance outside the edges of the plume itself.…”
Section: Seviri Sensor and Retrievals Strategies Descriptionmentioning
confidence: 99%
“…For the distal monitoring, VCTH is computed by applying the same procedure described for the VPTH parameter but considering the whole volcanic cloud, while the ash and SO 2 detection and retrievals are obtained by exploiting the SEVIRI channels centred at 8.7, 10.8, and 12 µm (SEVIRI channels 7, 9, and 10, respectively). The detection is realized through a Red Green Blue (RGB) composite obtained by combining the brightness temperatures (T b ) of the three SEVIRI channels (R: T b,8.7 -T b,10.8 ; G: T b,12 -T b,10.8 ; B: T b,10.8 ), while the quantitative estimation of the different ash and SO 2 parameters are computed by exploiting the Volcanic Plume Retrieval (VPR) procedure, formerly Volcanic Plume Removal [16][17][18]50]. VPR requires in input only the VCTH and is based on the computation of a new image by replacing the radiance values in the region occupied by the plume with those obtained from a simple linear regression of the radiance outside the edges of the plume itself.…”
Section: Seviri Sensor and Retrievals Strategies Descriptionmentioning
confidence: 99%
“…The SVM technique was already applied to volcano monitoring, and it was demonstrated that it provides successful results [ 71 , 72 ], due to its high performance and lower computation costs. Until now, algorithms and models have been developed for the retrieval of the components of a volcanic cloud [ 73 , 74 , 75 ] but without the implementation of artificial intelligence approaches. However, machine learning and deep learning techniques have been exploited mainly for the detection of a volcanic cloud [ 63 , 66 , 76 , 77 ].…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative ESPs from SEVIRI data are derived using the volcanic plume retrieval algorithm to estimate the amount of fine ash and also SO 2 carried by volcanic clouds (VPR; [7,29,[54][55][56]). This procedure allows removing the detected volcanic cloud from satellite images by a linear interpolation of the radiances at the plume edges.…”
Section: Erupted Mass and Grain-size Distributionmentioning
confidence: 99%